Toward An Effective Strategy for Quality Assurance in Scientific Research in Arabic World - Mohammad Altaie (University of Science and Technology, Yemen, 2012)
Abstract The science system has become much more complex and more demanding for researchers over the past decades. There has been an increasing contextual influence, from government, industry and society at large. This development has consequences for evaluation systems, not those regarding the individual researcher or groups and projects, but also concerning the system as a whole. ًWe issued this research  after analyzing the state of the art of the evaluation of scientific research. The Study  came to the conclusion that the current régime of evaluations in the Jordan,  but also in other Arab countries, is perceived by many as too complex and too burdensome. Moreover, most systems lack the flexibility necessary to judge the quality of the variety of disciplines and their dynamic development in multi-, inter-, and transdisciplinary endeavors. With regard to the current system, the study recommends that there are two pivotal issues that need improvement. - Simplification of procedures, both in requirements and in sheer number. There are too many, non standardised and partly overlapping evaluations. On top of that, there is a lack of mutual attunement. -Fairness. The system should be able to do justice to the variety of disciplines and developments in research; and it should reflect the differences in research practices. At the end of this study, we  suggests a strategy to improve the current national evaluation system in the Arab countries, the so-called New Scientific Research Quality Assurance System (NSR-QAS). The study proposes a concise list of suggestions that together should be appropriate to meet the two major concerns mentioned above, the study advises a minimum number of indicators and / or a maximum amount of text, in order not to overburden the research group or the evaluation committee. The study hopes that the suggestions made in this research will be taken into account when designing the New Scientific Research Quality Assurance System